Az esélyegyenlőség és a fogyatékkal élők helyzetének területi különbségei Magyarországon - Fabula, Szabolcs (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
People with disabilities is one of the most marginal groups in today’s society so ensur-ing their rights and needs is a great challenge for policy makers and planners. This paper reviews the most important agreements and laws about disability in the European Union and Hungary, as well as the New Hungary Development Plan. Later the paper also reveals the spatial differences of the people with disabilities in Hungary on the regional scale and presents relationship between the state of development and the ratio of disabled people. In comparing the data of the country and the South Great Plain the charasteristics of the dis-abled population in age, qualification and employment are also highlighted. Finally there is a short summary of the accessible and non-accessible public buildings in Békés County and Békéscsaba.